Adverse effects of Hif1a mutation and maternal diabetes on the offspring heart - Cerychova, Radka; Bohuslavova, Romana; Papousek, Frantisek; Sedmera, David; Abaffy, Pavel; Benes, Vladimir; Kolar, Frantisek; Pavlinkova, Gabriela (Cardiovascular diabetology, 2018)
BACKGROUND: Epidemiological studies show that maternal diabetes predisposes offspring to cardiovascular and metabolic disorders. However, the precise mechanisms for the underlying penetrance and disease predisposition remain poorly understood. We examined whether hypoxia-inducible factor 1 alpha, in combination with exposure to a diabetic intrauterine environment, influences the function and molecular structure of the adult offspring heart. METHODS AND RESULTS: In a mouse model, we demonstrated that haploinsufficient (Hif1a+/-) offspring from a diabetic pregnancy developed left ventricle dysfunction at 12 weeks of age, as manifested by decreased fractional shortening and structural remodeling of the myocardium. Transcriptional profiling by RNA-seq revealed significant transcriptome changes in the left ventricle of diabetes-exposed Hif1a+/- offspring associated with development, metabolism, apoptosis, and blood vessel physiology. In contrast, both wild type and Hif1a+/- offspring from diabetic pregnancies showed changes in immune system processes and inflammatory responses. Immunohistochemical analyses demonstrated that the combination of haploinsufficiency of Hif1a and exposure to maternal diabetes resulted in impaired macrophage infiltration, increased levels of advanced glycation end products, and changes in vascular homeostasis in the adult offspring heart. CONCLUSIONS: Together our findings provide evidence that a global reduction in Hif1a gene dosage increases predisposition of the offspring exposed to maternal diabetes to cardiac dysfunction, and also underscore Hif1a as a critical factor in the fetal programming of adult cardiovascular disease.
Keywords: Prenatal Exposure Delayed Effects; Ventricular Function, Left; mutace; funkce levé komory srdeční; Mice, Knockout; Risk Factors; vývojová regulace genové exprese; zpožděný efekt prenatální expozice; Heart remodelling; experimentální diabetes mellitus; Gene Expression Regulation, Developmental; Pregnancy; těhotenství; Myocardium; haploinsuficience; Echocardiography; faktor 1 indukovatelný hypoxií - podjednotka alfa; Ventricular Remodeling; Maternal diabetes; myši knockoutované; kardiovaskulární nemoci; Diabetes, Gestational; Animals; ženské pohlaví; gestační diabetes; interakce genů a prostředí; zvířata; rizikové faktory; Gene-Environment Interaction; Hif1a haploinsufficiency; Diabetes Mellitus, Experimental; Cardiovascular Diseases; Mutation; Fetal programming; Hypoxia-Inducible Factor 1, alpha Subunit; Female; Haploinsufficiency; remodelace komor; myokard